George Santayana's philosophy of religion: his Roman Catholic influences and phenomenology - Lovely, Edward W. (Lexington Books, 2013)
A paradoxical "Catholic" naturalist -- The philosophical basis for Santayana's philosophy of religion -- The phenomenological character of Santayana's philosophy of the Spirit -- The coherent nature of Santayana's philosophy of religion -- Aspects of Santayana's legacy to religious studies in the third millennium